The role of rootstock and its genetic background in plant mineral status: the relationship between petiole analyses and deficiency symptoms - Morel, Marine; Cookson, Sarah Jane; Da Costa, Jean-Pierre; Ollat, Nathalie; Marguerit, Elisa (OENO one, 2024)
Rootstocks are an important means of adapting grapevine to environmental conditions whilst conserving the typical features of scion genotypes. Rootstocks not only provide tolerance to Phylloxera, but also ensure the supply of water and mineral nutrients to the scion. We take advantage of the large diversity of rootstocks used worldwide to facilitate this adaptation. The aim of this study was to characterise rootstock regulation of scion mineral status and its relationship with scion development.Vitis vinifera cvs. Cabernet-Sauvignon, Pinot noir, Syrah and Ugni blanc were grafted onto 55 different rootstock genotypes and planted as three replicates of five plants in sandy gravelly soil near Bordeaux, France. In 2020 and 2021, petiolar concentrations of 13 mineral elements (N, P, K, S, Mg, Ca, Na, B, Zn, Mn, Fe, Cu and Al) were measured at veraison. Winter pruning weight, shoot vigour, leaf chlorophyll content, bud fertility and yield were measured. Magnesium deficiency severity was visually scored for each plant. Rootstocks were grouped according to their Vitis parentage background when at least 50 % of a Vitis species was present in order to determine whether the petiole mineral composition could be related to the rootstock genetic parentage.Scion, rootstock, and their interactions had a significant influence on petiole mineral content and explained the same proportion of phenotypic variance for most mineral elements. Rootstock effect explained 9, 28 and 45 % of the mineral content variance for N, Mg and S respectively. This unique experimental design showed that the rootstock effect was higher than the scion effect on the petiole concentration of a large majority of mineral elements. The genetic background V. riparia increased the probability of low petiolar P and Mg contents. The severity of Mg deficiency symptoms varied depending on the rootstock. The differences in mineral status conferred by rootstocks were not significantly correlated with vigour or fertility.The evaluation of Mg levels by petiole analysis and the intensity of deficiency symptoms showed for the first time the variability of the thresholds of satisfactory mineral nutrition between rootstocks. Therefore, fertiliser management should take the rootstock variety into account.